Early Metallurgy of the Persian Gulf : Technology, Trade, and the Bronze Age World - Weeks, Lloyd, (American School of Prehistoric Research Monograph Series ;, 2003)
This volume examines the earliest production and exchange of copper and its alloys in the Persian Gulf, a major metal supply route for the Bronze Age societies of Western Asia. Weeks addresses the geological and technological background to copper production in southeastern Arabia and contextualizes evidence for major fluctuations in prehistoric copper production. The core of the volume contists of compositional and isotopic analyses. The relationship between specialized copper production, exchange, and the development of social complexity in early Arabia is examined, and the author addresses the broader archaeological issue of the Bronze Age tin trade, which linked vast areas of Western Asia, from the Indo-Iranian borderlands to the Aegean, in the third millennium BC.